2010
DOI: 10.1086/653052
|View full text |Cite
|
Sign up to set email alerts
|

Use of Severity Scoring and Stratification Factors in Clinical Trials of Hospital‐Acquired and Ventilator‐Associated Pneumonia

Abstract: Clinical studies of hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) enroll patients with a very wide spectrum of disease, in part, related to the patient and/or host, the causative pathogen, and the severity of the pulmonary disease, severity of illness, and other comorbidities. Studies have identified the presence of some baseline variables (eg, Acute Physiologic Assessment and Chronic Health Evaluation II score Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…This study compared their usefulness in evaluating patients presenting to the authors' hospital with clinical manifestations suggestive of influenza infection during the influenza A (H1N1)pdm09 pandemic. Three of the most common clinical scores-CURB-65, APACHE II, and SOFA-were evaluated, all of which have been used to evaluate the severity of viral and bacterial CAP (15,19,31). Recently, studies demonstrated that CURB-65 is not a good predictor of the severity of pneumonia caused by influenza A (H1N1)pdm09 (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…This study compared their usefulness in evaluating patients presenting to the authors' hospital with clinical manifestations suggestive of influenza infection during the influenza A (H1N1)pdm09 pandemic. Three of the most common clinical scores-CURB-65, APACHE II, and SOFA-were evaluated, all of which have been used to evaluate the severity of viral and bacterial CAP (15,19,31). Recently, studies demonstrated that CURB-65 is not a good predictor of the severity of pneumonia caused by influenza A (H1N1)pdm09 (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of CPIS is limited in surgical, trauma, and burn patients, as CPIS was unable to differentiate VAP from systemic inflammatory response syndrome. 54 Furthermore, the utility of the modified CPIS to diagnose VAP was assessed in 740 subjects enrolled in a multi-center randomized trial, and no CPIS threshold was clinically useful (receiver operating characteristic area under the curve 0.47, 95% CI 0.42-0.53). 55 The authors concluded that early tracheostomy (performed after 6 -8 d of endotracheal intubation) did not result in significant reduction in the incidence of VAP compared with late tracheostomy (performed after 13-15 d of endotracheal intubation) and was associated with an adverse event related to the tracheostomy procedure in more than one third of subjects.…”
Section: Large Retrospective Cohort Studymentioning
confidence: 99%
“…For adults, the Clinical Pulmonary Infection Score and similar scoring systems have been used to describe severity of infection and prognosis [21]. Such scoring systems have been used to describe the natural history of disease and have the potential to assess the benefit of investigational therapy.…”
Section: Clinical Trial Issues Exclusive To Childrenmentioning
confidence: 99%